2018
DOI: 10.3847/1538-3881/aacb1f
|View full text |Cite
|
Sign up to set email alerts
|

Li in Open Clusters: Cool Dwarfs in the Young, Subsolar-metallicity Cluster M35 (NGC 2168)*

Abstract: Hydra spectra of 85 G-K dwarfs in the young cluster, M35, near the Li 6708Å line region are analyzed. From velocities and Gaia astrometry, 78 are likely single-star members which, combined with previous work, produces 108 members with T eff ranging from 6150 to 4000 K as defined by multicolor, broadband photometry, E(B − V ) = 0.20 and [Fe/H] = -0.15, though there are indications the metallicity may be closer to solar. A(Li) follows a well-delineated decline from 3.15 for the hottest stars to upper limits ≤ 1.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 95 publications
(141 reference statements)
3
13
0
Order By: Relevance
“…Therefore, the main conclusion of this study is that we do not see any evidence of a decrease in Li at supersolar metallicity. Rather, the opposite might be true, and the data may suggest a positive Li versus [Fe/H] trend, in agreement with the suggestions of Anthony-Twarog et al (2018). Whilst a Bayesian analysis also supports a positive Li versus Fe correlation, this needs to be confirmed with a larger number of clusters, in particular young ones in the metal-poor regime.…”
Section: Resultssupporting
confidence: 75%
“…Therefore, the main conclusion of this study is that we do not see any evidence of a decrease in Li at supersolar metallicity. Rather, the opposite might be true, and the data may suggest a positive Li versus [Fe/H] trend, in agreement with the suggestions of Anthony-Twarog et al (2018). Whilst a Bayesian analysis also supports a positive Li versus Fe correlation, this needs to be confirmed with a larger number of clusters, in particular young ones in the metal-poor regime.…”
Section: Resultssupporting
confidence: 75%
“…As for cooler, lower-mass stars, in intermediate-age clusters, recent WOCS observations of M35 have shown that this cluster behaves similarly to the younger Pleiades, since a dispersion in Li is seen among cool stars, as well as a relationship with rotation and radii (Anthony- Twarog et al, 2018a;Jeffries et al, 2020); this, on the one hand, provides some support for models with inflated radii and lower Li depletion in the faster rotators (more active stars), as discussed above. At the same time, the authors claim that rotational mixing cannot be excluded: given the saturation of magnetic activity, stars would have similar levels of activity, and Li depletion during the PMS may be inhibited for all of them, while additional mixing would subsequently deplete more Li in slow rotators that undergo angular momentum loss (Jeffries et al, 2020).…”
Section: The Ms Phasesmentioning
confidence: 99%
“…b than 1 Gyr. The main recent results on Li evolution during the MS have been summarized byTwarog et al (2020) (see alsoDeliyannis et al, 2019;Anthony-Twarog et al, 2018a, Anthony-…”
mentioning
confidence: 97%
“…On average, the older the star the worse the discrepancy, with the Sun being one of the most egregious offenders, having depleted a factor of 50 more Li than the factor of ∼ 3 predicted by the SSET (King et al 1997;Pinsonneault 1997;Asplund et al 2009;Thévenin et al 2017). Another example is that of lower mass stars in the pre-main sequence and early MS phase, which exhibit large dispersions in Li at the same mass and age, with rapid rotators exhibiting higher Li abundances (Somers & Pinsonneault 2014Bouvier et al 2018;Anthony-Twarog et al 2018b). A particularly distressing example is F dwarfs, in which deep envelope SCZs should not exist.…”
Section: Introductionmentioning
confidence: 99%